Cover Picture: Photoexcited Porphyrins as a Strong Suppressor of β‐Amyloid Aggregation and Synaptic Toxicity (Angew. Chem. Int. Ed. 39/2015). Issue 39 (21st August 2015) - Lee, Byung Il; Lee, Seongsoo; Suh, Yoon Seok; Lee, Joon Seok; Kim, Ae‐kyeong; Kwon, O‐Yu; Yu, Kweon; Park, Chan Beum
Abstract : Photoexcited porphyrin molecules inhibit β‐amyloid aggregation and rescue postsynaptlc toxicity and behavior defects in the Drosophila Alzheimer's disease model under blue light. In their Communication on page 11472 ff., C. B. Park, K. Yu et al. present a chemical strategy for photodynamic suppression of β‐amyloid aggregation using photosensitizing molecules.